The impact of product cues and attitude towards brand towards purchase intention of automobiles - Hashim, Noor Azmi; Mohamad, Osman; Haron, Mahmod Sabri (2014)
The varying characteristics reflective of the actual diversity in how intentions are conducted have found that intentions are significantly better predictors of purchase behavior for existing products and for durable than for non-durable products.These results are remarkable because in practice, intentions are often used to predict sales for new non-durable products and also that intentions are better predictors of behaviors over short that over long time horizons.Branding is also important because it communicates a brand’s business proposition.The most successful visual expression of a brand is its core attributes and it needs to establish a positive emotional relationship between the brand and its audiences.